1992
DOI: 10.3109/01421599209018858
|View full text |Cite
|
Sign up to set email alerts
|

Anatomy of the upper limb: A partnership in learning and assessment

Abstract: Specific rehabilitation of the upper limb by the Occupational Therapist requires a sound working knowledge of the anatomy of the pectoral girdle, arm, forearm and hand. To aid the learning process the Liverpool occupational therapy students are given their assessment topics at the beginning of the course. They find a conductive partner with whom to work and practice, and together they prepare for the oral demonstration which forms the assessment test at the end of the second term. Each student completes a ques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Learner Psychological Considerations. One quasi-experimental study and two cross-sectional studies found that strategies to provide psychological support prior to participation in gross anatomy labs and practical examinations were helpful in reducing learner anxiety ( Chaudhuri, 2021a ; Romo-Barrientos et al, 2019 ; Tyldesley, 1992 ), improving satisfaction with the learning experience ( Romo-Barrientos et al, 2019 ; Tyldesley, 1992 ), and were associated with higher academic performance ( Chaudhuri, 2021a ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Learner Psychological Considerations. One quasi-experimental study and two cross-sectional studies found that strategies to provide psychological support prior to participation in gross anatomy labs and practical examinations were helpful in reducing learner anxiety ( Chaudhuri, 2021a ; Romo-Barrientos et al, 2019 ; Tyldesley, 1992 ), improving satisfaction with the learning experience ( Romo-Barrientos et al, 2019 ; Tyldesley, 1992 ), and were associated with higher academic performance ( Chaudhuri, 2021a ).…”
Section: Resultsmentioning
confidence: 99%
“…Evaluation approaches reported in this review were largely traditional formats involving written tests with multiple choice questions, practical exams, and bellringer exams to test cadaver-based information. The use of small group learning and peer mentorship reported by some authors was representative of alternate means of expression and feedback ( de Oliveira et al, 2015 ; Tyldesley, 1992 ); however, an overall lack of diversity in learner assessment methods was reported in occupational therapy anatomy education literature. Individual and group evaluations that allow students to demonstrate and apply their knowledge through oral, visual, kinesthetic, or written indicators support different avenues of expression and consolidation of learning.…”
Section: Discussionmentioning
confidence: 99%